Hubungan Kebiasaan Menyikat Gigi dengan Kebersihan Gigi dan Mulut - Agmeistiya Mawarni; Eliza Herijulianti; Devy Octaviana; Ulfah Utami (Poltekkes Kemenkes Bandung, 2022)
Dental and oral health is an inseparable part of body health, because it will affect the overall health of the body. Children with special needs, one of them is blind, who has a condition with impaired vision that requires assistance in maintaining personal hygiene, especially dental and oral hygiene. This study aims to determine the relationship between brushing habits and oral hygiene in blind people at SLB Citeureup, Cimahi City. This study uses an analytical survey method with a cross sectional design. The research was conducted at SLB Citeureup, Cimahi City. Blind population with a sample of 17 respondents who were determined using the Slovin formula. Data analysis in this study used the Kendall's Tau correlation test with hypothesis testing based on a significance level of <0.05 with a 95% confidence level. The results showed that there was a relationship between brushing habits and oral and dental hygiene in the visually impaired, this was indicated by a p value of 0.018. It can be concluded that the hypothesis which states that there is a relationship between brushing habits and oral hygiene in blind children can be accepted because basically the intelligence abilities of blind children are the same as normal children, but if the ability to brush teeth of blind children does not eat well, it affects oral hygiene.